2017
DOI: 10.1111/apa.13779
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric approaches to child maltreatment are subject to wide organisational variations across Europe

Abstract: Aim: Little is known about the organisation of child maltreatment practice in Europe. We therefore explored medical child protection systems and training across Europe.Methods: An online survey was completed by physicians working in child maltreatment, identified through professional organisations in 28 member countries of the European Union, Iceland, Norway and Switzerland in 2012-2013. Respondents were questioned regarding management of suspected child maltreatment, mandatory reporting, professional training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This could reflect the wide variations in the organisation of child maltreatment paediatrics in Europe as described by Otterman et al . (). The authors stress the importance of considering the differing legislative frameworks and models of care across Europe when comparing epidemiology in child maltreatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This could reflect the wide variations in the organisation of child maltreatment paediatrics in Europe as described by Otterman et al . (). The authors stress the importance of considering the differing legislative frameworks and models of care across Europe when comparing epidemiology in child maltreatment.…”
Section: Discussionmentioning
confidence: 97%
“…Otterman et al . () suggest that only a small minority of represented countries in Europe have established systematic requirements for the education of physicians on child maltreatment. Others have shown the positive impact of subject‐specific training (Herbst et al ., ) and specialisation (Furth et al ., ) on clinical decision‐making and subsequent management.…”
Section: Discussionmentioning
confidence: 99%
“…Teamwork in child abuse diagnostics in itself is not a novel development. In many countries, the hospitals have some form of a hospital-based multidisciplinary team, and these have proven their value over time 9–12. Besides these hospital-based teams, many countries, as well as The Netherlands, have initiated regional or citywide rape and sexual abuse counselling centres, where in many cases specially trained sexual assault nurse examiners and/or child abuse paediatricians work 13–15.…”
Section: Discussionmentioning
confidence: 99%
“…A survey completed by physicians working with maltreated children in 22 European countries showed that there were wide variations in how the units dealing with this trauma were organised . The authors, Otterman et al., suggest that European children would probably benefit from a more unified organisational framework that includes standardised training for physicians.…”
Section: Paediatric Approaches To Child Maltreatment Vary Across Europementioning
confidence: 99%